2020
DOI: 10.3390/su12093714
|View full text |Cite
|
Sign up to set email alerts
|

High Plains Aquifer–State of Affairs of Irrigated Agriculture and Role of Irrigation in the Sustainability Paradigm

Abstract: Groundwater depletion is a serious issue in the southern and central parts of the High Plains Aquifer (HPA), USA. A considerable imbalance exists between the recharge process and groundwater extractions in these areas, which threatens the long-term sustainability of the aquifer. Irrigated agriculture has a major share in the economy, and it requires high pumping rates in regions vulnerable to large groundwater level declines. A literature review has been conducted to understand the state of affairs of irrigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…Like pumping, annual deep percolation values were uniformly disaggregated to daily values over the 103-day pumping period. This assumption is justified because essentially all deep percolation in the area is the result of excess applied irrigation water (Ajaz et al, 2020).…”
Section: Model Construction and Input Datamentioning
confidence: 99%
“…Like pumping, annual deep percolation values were uniformly disaggregated to daily values over the 103-day pumping period. This assumption is justified because essentially all deep percolation in the area is the result of excess applied irrigation water (Ajaz et al, 2020).…”
Section: Model Construction and Input Datamentioning
confidence: 99%
“…In a study Lamm and Trooien 50 were also reported 35–55% saving of irrigation water under SSDI over FI. The reduction in irrigation requirement in SSDI plots was mainly because of reduced soil evaporation, decreased deep percolation and elimination of runoff losses 51 . Overall, in the present study, SSDI coupled with CA-practices at sufficient N application resulted in the highest moisture content, lowest variability the most effective root-zone layer (15–30 cm soil depth).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with this, various techniques are being used to solve food security and water supply issues for multiple uses and ensure an environmental balance [7][8][9]. Some studies in the literature suggested creating water demand management measures [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Smart irrigation could be one feasible solution in the context of efficient water management. Assessing the overall water availability, preparing coping mechanisms for drought times, improving irrigation scheduling tools, and combining the technology and management techniques should be considered when upgrading the irrigation systems [11]. Smart irrigation management helps to detect when to irrigate, the amount of water required, and the irrigation frequency, based on the monitoring of crop evapotranspiration and soil moisture situations [12].…”
Section: Introductionmentioning
confidence: 99%